Analisis Rantai Nilai Kopi pada Yayasan Mukmin Mandiri Sidoarjo: Coffee Value Chain Analysis at the Mukmin Mandiri Foundation in Sidoarjo - Khairunisak, Atiqah Syilvia; Winarno, Sri Tjondro (Jurnal Ilmiah Manajemen Agribisnis, 2023)
The purpose of this study is 1) Mapping the value chain of coffee products at the Mukmin Mandiri Sidoarjo. 2) Identify the relations between the value chains and the role of each actor involved in Mukmin Mandiri Sidoarjo. 3) Knowing the added value of coffee products at the Mukmin Mandiri Sidoarjo. The method of analysis used in this research is the descriptive qualitative method. According to Kaplinsky and Morris (2001), data analysis consists of value chain analysis and cost and value- added analysis, according to Hayami Method. Mukmin Mandiri Sidoarjo has four chain actors in the chain, and they are farmers, Mukmin MandiriSidoarjo itself, distributors, and agents. The added value obtained from the production of ground coffee at the Mukmin Mandiri Sidoarjo is Rp12,588.4 per kilogram of raw material or about 37.82% of the product value per unit of raw material, and the profit obtained from the production of ground coffee at Mukmin Mandiri Rp21,500 per kilograms